The Influence of Identity Politics on Elections and Policy Making - LOKESH (Innovative Research Thoughts, 2023)
Identity politics is a complicated and varied phenomena that has been more prominent in recent years. Its effect on elections and policy making is a phenomenon that has gotten increasingly significant. The concept of identity politics is based on the notion that the social and cultural identities of people, such as their race, gender, religion, and sexual orientation, play a substantial influence in the formation of their political opinions and affiliations. During elections, politicians often make an effort to appeal to certain identity groups by customising their messaging and policy ideas to connect with the concerns and interests of these groups. The creation of voting blocs that have the potential to influence the outcome of an election might potentially result from this. On top of that, identity politics has the potential to influence the objectives and agendas of elected officials, which in turn may have an effect on policymaking. There is a possibility that policymakers would prioritise topics that are significant to their constituency or identity group. This can have an effect on the distribution of resources and the formulation of laws. On the other hand, the impact of identity politics on elections and the formulation of public policy raises significant concerns regarding representation and inclusivity. This is because identity politics can sometimes result in a concentration on the interests of particular identity groups at the expense of those of other groups. One of the challenges that nations all over the globe continue to struggle with is finding a way to strike a balance between acknowledging the valid concerns of various identity groups and supporting a democratic system that is more inclusive and equal.